Pembuatan Media Pembelajaran Interaktif Bahasa Inggris Untuk Siswa SMPN Satap 1 Batukliang - Zulkarnaen, Muhammad Fauzi; Zaen, Mohammad Taufan Asri; Dewi, Trisna (Jurnal Ilmiah IKIP Mataram, 2020)
There is a tendency in some schools, especially Junior High School One Roof (SMPN SATAP) 1 Batukliang implement a learning model that is conventional, so that the delivery of the material taught to be less effective and the students become less able to digest quickly the material presented and just focus on knowledge in the book. It is therefore in need of a computerized system for greater ease in delivery of material that is easy to understand in the implementation of teaching and learning.System development method used in the design and construction of the system is a method of system development SDLC (Systems Development Life Cycle) which is an evolutionary process that is followed in implementing the system or sub-system of computer-based information. To get a system that is always good, so do some of the process: planning, analysis, design, implementation, testing and maintenance. As for building a system using the PHP programming language and MySQL database. From the analysis, system design and manufacture of the application, then the application can improve students' learning spirit as it can assist teachers in delivering materials English lessons so that students more easily understand English studies with a more interactive learning methods.